MENINGKATKAN KETERAMPILAN MENYIMAK MENGGUNAKAN METODE STORY TELLING PADA MUATAN BAHASA INDONESIA SISWA KELAS V SDN 162 SEJINJANG KOTA JAMBI - Nur Azizah; Irzal Anderson; Muhammad Sholeh (LPPM STKIP Bina Bangsa Meulaboh, 2024)
Listening skills are language skills that are included in receptive language, meaning they are skills that must be mastered by children as a basis for other language skills. One method that can make children active and happy is by using the story telling method. This research aims to describe the improvement of students' listening skills through the story telling method in Indonesian language content for class V students at SDN 162 Sejinjang, Jambi City. The approach in this research uses classroom action research. The results of this research found that there was an increase in listening skills in cycle I and cycle II. In cycle II there was an increase in the learning process by applying the story telling learning model. From this research, it is recommended that teachers in implementing story telling model learning, teachers should give more opportunities and special attention to students who are less enthusiastic in the learning process to convey their opinions so that they can train courage in students.